Molecular and Functional Characterization of ssDNA Aptamers that Specifically Bind Leishmania infantum PABP. - Natalia Guerra-Pérez; Edurne Ramos; Marta García-Hernández; Celia Pinto; Manuel Soto; M Elena Martín; Víctor M González (PLoS ONE, 2015)
A poly (A)-binding protein from Leishmania infantum (LiPABP) has been recently cloned and characterized in our laboratory. Although this protein shows a very high homology with PABPs from other eukaryotic organisms including mammals and other parasites, exist divergences along the sequence that convert them in potential diagnostic markers and/or therapeutics targets. Aptamers are oligonucleotide ligands that are selected in vitro by their affinity and specificity for the target as a consequence of the particular tertiary structure that they are able to acquire depending on their sequence. Development of high-affinity molecules with the ability to recognize specifically Leishmania proteins is essential for the progress of this kind of study.We have selected a ssDNA aptamer population against a recombinant 6xHIS-LiPABP protein (rLiPABP) that is able to recognize the target with a low Kd. Cloning, sequencing and in silico analysis of the aptamers obtained from the population yielded three aptamers (ApPABP#3, ApPABP#7 and ApPABP#11) that significantly bound to PABP with higher affinity than the naïve population. These aptamers were analyzed by ELONA and slot blot to establish affinity and specificity for rLiPABP. Results demonstrated that the three aptamers have high affinity and specificity for the target and that they are able to detect an endogenous LiPABP (eLiPABP) protein amount corresponding to 2500 L. infantum promastigotes in a significant manner. The functional analysis of the aptamers also revealed that ApPABP#11 disrupts the binding of both Myc-LiPABP and eLiPABP to poly (A) in vitro. On the other hand, these aptamers are able to bind and purify LiPABP from complex mixes.Results presented here demonstrate that aptamers represent new reagents for characterization of LiPABP and that they can affect LiPABP activity. At this respect, the use of these aptamers as therapeutic tool affecting the physiological role of PABP has to be analyzed.